Loved and missed - Boyt, Susie, 1969- (The New York Review of Books, 2021)
"When your beloved daughter is lost in the fog of addiction and you make off with her baby in order to save the day, can willpower and a daring creative zeal carry you through? Examining the limits, disappointments and excesses of love in all its forms, this marvellously absorbing novel, full of insight and compassion, delights as much as it disturbs"--